PEMBERDAYAAN MASYARAKAT DAYAK ASLI (KANAYATN) MELALUI MPLEMENTASI PENDAMPINGAN DESA SIAGA, AKSES PENDIDIKAN DAN SOSIAL EKONOMI - Elly Trisnawati (Jurnal Buletin Al-Ribaath, 2018)
ABSTRACTLandak is one of the district with some area still far from optimal conditions, either  health, education, nor economic sectors. Most of the people of Landak has graduated on elementary school (>50%), PHBS (Clean and Healthy Living Behaviour)  problems become priority in health field. The economic conditions is in middle to lower category . One of the area in Landak, which still require efforts to improve human resources is Mempawah Hulu District which is dominated by Dayak Kanayatn tribe. The purpose of KKN-PPM activities in Kecamatan (Sub District) Mempawah Hulu is to empower the community in health, education and socio-economic sectors . The method implemented in order to  empower the society ,  by a trigger role form and community , institutional reinforcement and community mobilization. Third partys  in this activity is Kecamatan Mempawah Hulu along with three villages in the region districts and Puskesmas (Public Helath Center) Karangan. Through these activities, Alert village  could be activated again. Establishment of PHBS (Clean and Healthy Living Behaviour) cadres, cadres Alert , pioneer of GENRE as well as an initiation of ODF hamlet can implemented . In the fields of education, it is formed reading house thet has the synergy with  green school  and formation  learning group. In field of entrepreneurship, it is formed a catfish cultivation group and chicken boiler cultivation group  as well formed group of  entrepreneurship that has a society priority within its products originated from ingredients local . The expectation is that from  the whole program has initiated, will be able to be applied on sustainable in three villages, namely Pahokng Village , Caokng and TunangKeyword : empowerment, alert village, entrepreneurship , Dayak Kanayatn